Pharmacist-Managed Refill Service Impacts on Clinician Workload and Medication Interventions in a Federally Qualified Health Center - Keri Hurley-Kim; Azin Keyvani; Raed Ahmed; Hei-Wah Wong; Sarah McBane (SAGE Publishing, 2023)
Introduction: Increasing administrative workload is linked with lower quality of patient care and physician burnout. Conversely, models involving pharmacists can positively impact patient care and physician well-being. Research has consistently demonstrated that pharmacist-physician collaboration can improve outcomes for chronic diagnoses. Pharmacist-managed refill services may improve provider workload measures and clinical outcomes. Methods: This was an evaluation of a pharmacist-managed refill service at a Federally Qualified Health Center (FQHC). Under collaborative practice agreement, pharmacists addressed refill requests and recommended interventions. Data analysis evaluated effectiveness of the model, including clinical interventions, and involved descriptive statistics and qualitative approaches. Results: Average patient age was 55.5 years old and 53.1% were female. Turnaround time was within 48 h for 87.8% of refill encounters. During an average of 3.2 h per week, pharmacists addressed 9.2% (n = 1683 individual requests in 1255 indirect patient encounters) of the total clinic refill requests during the 1-year study period. In 453 of these encounters (36.1%), pharmacists recommended a total of 642 interventions. 64.8% of these were need for appointment (n = 211) or labs (n = 205). Drug therapy problems and medication list discrepancies were identified in 12.6% (n = 81) and 11.9% (n = 76) of encounters, respectively. Discussion and Conclusions: The results of this study are consistent with previous literature demonstrating the value of interprofessional collaboration. Pharmacists addressed refills in an efficient, clinically effective manner in an FQHC setting. This may positively impact primary care provider workload, patients' medication persistence, and clinical care.